Determination of polarization fields in group III-nitride heterostructures by capacitance-voltage-measurements - Rychetsky, Monir; Koslow, Ingrid; Avinc, Baran; Rass, Jens; Wernicke, Tim; Bellmann, Konrad; Sulmoni, Luca; Hoffmann, Veit; Weyers, Markus; Wild, Johannes; Zweck, Josef; Witzigmann, Bernd; et al. (Journal of Applied Physics, 2016)
The polarization fields in wurtzite group III-nitrides strongly influence the optical properties of InAlGaN-based light emitters, e.g., the electron and hole wave function overlap in quantum wells. In this paper, we propose a new approach to determine these fields by capacitance-voltage measurements (CVM). Sheet charges generated by a change of the microscopic polarization at heterointerfaces influence the charge distribution in PIN junctions and therefore the depletion width and the capacitance. We show that it is possible to determine the strength and direction of the internal fields by comparing the depletion widths of two PIN junctions, one influenced by internal polarization fields and one without as a reference. For comparison, we conducted coupled Poisson/carrier transport simulations on the CVM of the polarization-influenced sample. We also demonstrate the feasibility and limits of the method by determining the fields in GaN/InGaN and GaN/AlGaN double heterostructures on (0001) c-plane grown by metal organic vapor phase epitaxy and compare both evaluation methods. The method yields (-0.50 ± 0.07) MV/cm for In0.08Ga0.92N/GaN, (0.90 ± 0.13) MV/cm for Al0.18Ga0.82N/GaN, and (2.0 ± 0.3) MV/cm for Al0.31Ga0.69N/GaN heterostructures.
CRIS-Team Scopus Importer:2021-06-11